Concordance of HER2 expression in paired primary and metastatic sites of gastric and gastro-oesophageal junction cancers. Issue 7 (December 2015) - Wong, Daniel D.; Kumarasinghe, M. Priyanthi; Platten, Michael A.; de Boer, W. Bastiaan
Abstract : Summary: HER2 is amplified/overexpressed in a subset of gastric and gastro-oesophageal junction cancers. Addition of anti-HER2 therapy has been shown to provide survival benefit in this setting. However, there are limited data assessing the concordance of HER2 status between primary and metastatic sites. A total of 113 samples from 43 paired primary and metastatic tumours were tested for HER2 status, by immunohistochemistry (IHC) for protein expression and silver in situ hybridisation (SISH) for gene amplification. Primary sites tested included endoscopic biopsies ( n  = 30) and resections ( n  = 24). Metastatic samples included lymph nodes ( n  = 29), peritoneal effusions ( n  = 21) and miscellaneous sites ( n  = 9). The overall HER2+ rate was 11%. Of 41 (95%; 95% CI 88.5–100%) concordant cases, 38 were HER2– and three were HER2+. There were two (5%) discordant cases, one of which showed heterogeneity of HER2 expression. This series confirms a high concordance rate of 95%, supporting that testing of primary tumours and metastases is equally valid and providing clinical rationale for the addition of anti-HER2 therapy in HER2+ disseminated disease.